ANALISIS EFEK KEBIJAKAN MONETER TERHADAP OUTPUT DI INDONESIA - Catona Machtra; Fakhruddin Fakhruddin (Syiah Kuala University, 2016)
The purpose of this research is to analyze the relationship of Gross Domestic Product, Exchange Rate and Inflation. Analysis used multiple regression analysis instruments with Vector Autoregressive (VAR) model and using quarterly data from 1990.1 to 2015.4 periods. The results of this research show significant relationship between Gross Domestic Product, Exchange Rate, and Inflation. For the next research, the author suggests to employ different variables to further investigate relationship variables toward output in Indonesia.